Spontaneous In Situ Formation of Liposomes from Inert Porous Microparticles for Oral Drug Delivery - Maryam Farzan; Gabriela Québatte; Katrin Strittmatter; Florentine Marianne Hilty; Joachim Schoelkopf; Jörg Huwyler; Maxim Puchkov (MDPI AG, 2020)
Despite the wide-spread use of liposomal drug delivery systems, application of these systems for oral purposes is limited due to their large-scale formulation and storage issues. Proliposomes are one of the formulation approaches for achieving solid powders that readily form liposomes upon hydration. In this work, we investigated a dry powder formulation of a model low-soluble drug with phospholipids loaded in porous functionalized calcium carbonate microparticles. We characterized the liposome formation under conditions that mimic the different gastrointestinal stages and studied the factors that influence the dissolution rate of the model drug. The liposomes that formed upon direct contact with the simulated gastric environment had a capacity to directly encapsulate 25% of the drug in situ. The emerged liposomes allowed complete dissolution of the drug within 15 min. We identified a negative correlation between the phospholipid content and the rate of water uptake. This correlation corroborated the results obtained for the rate of dissolution and liposome encapsulation efficiency. This approach allows for the development of solid proliposomal dosage formulations, which can be scaled up with regular processes.